Numerical solution of fuzzy fractional pharmacokinetics model arising from drug assimilation into the bloodstream - Ahmadian, Ali; Senu, Norazak; Larki, Farhad; Salahshour, Soheil; Suleiman, Mohamed; Islam, Md. Shabiul (Hindawi Publishing Corporation, 2013)
We propose a Jacobi tau method for solving a fuzzy fractional pharmacokinetics. This problem can model the concentration of the drug in the blood as time increases. The proposed approach is based on the Jacobi tau (JT) method. To illustrate the reliability of the method, some special cases of the equations are solved as test examples. The method reduces the solution of the problem to the solution of a system of algebraic equations. Error analysis included the fractional derivative error estimation, and the upper bound of the absolute errors is introduced for this method.